Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1076/stra.7.1.1.656
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual acuity in children aged 1½-6 years, with normal and subnormal vision

Abstract: The aim of the study was to assess different visual acuity tests in the age group 1 1/2-6 years in 105 children with assumed normal vision, visual impairment due to ocular disease or strabismus. Acuity tasks for young children can be divided into three subtypes according to the kind of stimulus used. For "detection acuity", the stimulus should be detected or distinguished from the background, as assessed with the Stycar Rolling Balls. For "resolution acuity", the stimulus pattern should be resolved, as assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 15 publications
6
39
1
Order By: Relevance
“…However, a certain amount of crowding has been observed in normal children (Rydberg et al 1999;Dekker et al 2012) -something that was confirmed in the present study. The mean value of approximately 1.1 was somewhat lower than that found by Atkinson et al (1988) (1.2 at 5-7 years of age) and Dekker et al (2012) (1.3 at 6-12 years of age).…”
Section: Right Eye Left Eye Binocularsupporting
confidence: 80%
“…However, a certain amount of crowding has been observed in normal children (Rydberg et al 1999;Dekker et al 2012) -something that was confirmed in the present study. The mean value of approximately 1.1 was somewhat lower than that found by Atkinson et al (1988) (1.2 at 5-7 years of age) and Dekker et al (2012) (1.3 at 6-12 years of age).…”
Section: Right Eye Left Eye Binocularsupporting
confidence: 80%
“…The evaluation of visual function in infants remains difficult despite the availability of tests designed to circumvent lack of cooperation and verbal ability. 10,11 It is therefore customary to assess multiple parameters of visual function in studies in this age group. 11,14 In accordance with this principle we have assessed visual function by evaluating visual fixation and tracking, pupillary size and reaction, and assessment of the optic disc and integrated the results into a numerical scoring scale for ease of analysis and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Furthermore, in patients with cerebral visual impairment secondary to non-focal cerebral lesions, ultrasonographic appearance of the brain, visual, motor and cognitive functions are closely correlated. [9][10][11] and visual function can be an important predictor of cognitive development. The development of perceptual and motor skills also depends on visual function.…”
Section: Discussionmentioning
confidence: 99%
“…When possible, Snellen's optotype and Albini's E were used (Lueder and Garibaldi 1997); in preverbal age Pigassou's pictures (Pigassou and Pincon 1969) or Mentor-B vat's pictures were used as were the Vis Test and Bust Cards (Rydberg et al 1999). Keeler Acuity Cards or Visual Quotient (Salati 2001) was administered to children who found it difficult to cooperate.…”
Section: Ophthalmological Assessmentmentioning
confidence: 99%